2016
DOI: 10.1371/journal.pcbi.1004754
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rigidity Theory to the Thermostabilization of Lipase A from Bacillus subtilis

Abstract: Protein thermostability is a crucial factor for biotechnological enzyme applications. Protein engineering studies aimed at improving thermostability have successfully applied both directed evolution and rational design. However, for rational approaches, the major challenge remains the prediction of mutation sites and optimal amino acid substitutions. Recently, we showed that such mutation sites can be identified as structural weak spots by rigidity theory-based thermal unfolding simulations of proteins. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 93 publications
(144 reference statements)
1
65
0
Order By: Relevance
“…Kinetic analysis. To investigate effects of the mutations on enzyme kinetics, 4-nitrophenyl laurate (pNPL) hydrolysis was selected on the basis of its wide usage in lipase studies (61)(62)(63)(64), including those with LipT6 (47,48). The kinetic constants (Table 5) were calculated on the basis of activity under native conditions without methanol.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic analysis. To investigate effects of the mutations on enzyme kinetics, 4-nitrophenyl laurate (pNPL) hydrolysis was selected on the basis of its wide usage in lipase studies (61)(62)(63)(64), including those with LipT6 (47,48). The kinetic constants (Table 5) were calculated on the basis of activity under native conditions without methanol.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, strict rigidity theory based methods rely on exceedingly local motions to estimate conformational flexibility, 20,27,28 ligand binding, 31 entropy, 33,34 or thermo-stability 3840 compared to ENM or NMA. Nonetheless, they show convincing agreement with experimental data, if energy cutoffs to determine constraints are carefully chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring changes in protein rigidity from diluting the constraint network by gradually raising the energy threshold has informed on thermostability 3840 and the evolution of folding cores. 29,41 However, the topological and combinatorial nature of this approach denies explicit access to the kinematics of the underlying 3-dimensional molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…Residue X IV+1 has also been mentioned as part of the hydrophobic binding pocket [39] and the helical domain that occurs after strand β6 [20], while in some cases it can affect the enzymatic activity [42][43][44]. To our knowledge, there is only one mutational study that refers to residue X IV+1 , where its substitution has resulted in nearly complete loss of catalytic activity [45]. The tripeptide residue X IV -residue X IV+1 -residue X IV+2 retains its amino-acid conservation in some ABH fold enzyme families, and thus, it is suggested that it can be used as an additional sequence identifier of different ABH fold enzyme families [32,37].…”
Section: The Conserved Structural Elements That Line the Catalytic Stmentioning
confidence: 99%